KESANGGUPAN KECUBUNG (Datura metel) DALAM MENGHAMBAT MAKAN DAN MORTALITAS Plutella xylostella. L - Idris, Herwita (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
Cabbage (Brasssica oleracea) is a vegetable product that is very much needed by the community. However, in its exploitation always encountered obstacle because of pest attack. P. xylostella L (Lepidoptera: Plutellidae) is a major pest in cabbage farming. Control efforts are commonly done with synthetic insecticides, but this is considered less wise because usually the buildup of pesticide residues is very high, so less good for health. This study aims to determine the ability of amethyst plants (Datura metel) to inhibit the eating and mortality of Plutella xylostella. L on cabbage plants. The experiment was conducted at Laing Solok Experimental Laboratory (Balittro) from July to November 2017. The study used a complete randomized design (RAL) with 4 treatments and 6 replications, each treatment was amethys 4000, 5000, 7500 ppm and without extract (0 ppm) as control. Each treatment was applied to the larvae stadia used by instar II, III and IV, imago from P. xylostella insects. L. From the results obtained that the amethyst extract was able to increase mortality and inhibit the feeding of major insect pests on cabbage plants such as P. xylostella, So for the control of this pest can be done with the use of botanical insecticides, given the whole production of these plants are generally food-oriented. The amethyst extract has good insecticidal properties so it can influence the biological aspects of P. xylostella insects, Keywords: cabbage, Datura metel, P. xylostella, feeding inhibitor, mortality